EU private international law in family matters : legislation and CJEU case law / Costanza Honorati, Maria Caterina Baruffi. - Honorati, Costanza; Baruffi, M. C. (Maria Caterina) (Intersentia, 2023)
This volume collects all the relevant instruments in the field of EU private international law in family matters as completed by referencing all decisions issued by the CJEU on these regulations.